Function Cursor Y At
None
Format:
cursor y at time t
Input:
Output:
Conditional properties that reference this function:
if the following are true:
- value of cell 27 at time t = 1
- number of characters read at t < value of cell 26 at time t
then display text at x: (cursor x at time t), y: (cursor y at time t), and time: (t + 1) = value of cell (10 + (number of characters read at t)) at time t
(link)if the following are true:
- value of cell 27 at time t = 1
- number of characters read at t = value of cell 26 at time t
then cursor y at time (t + 1) = cursor y at time t
(link)if value of cell 27 at time t = 0, then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- value of cell 27 at time t = 1
- cursor x at time t < 39
then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- value of cell 27 at time t = 1
- cursor x at time t = 39
- cursor y at time t < 11
then cursor y at time (t + 1) = (cursor y at time t) + 1
(link)if cursor y at time t = 11, then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- value of cell 27 at time t = 1
- cursor x at time t = 39
- cursor y at time t = 11
then display text at x: x, y: y, and time: (t + 1) = display text at x: x, y: (y + 1), and time: t
(link)if the following are true:
- value of cell 27 at time t = 1
- value of cell (10 + (number of characters read at t)) at time t = 13
- cursor y at time t < 11
then cursor y at time (t + 1) = (cursor y at time t) + 1
(link)if the following are true:
- value of cell 27 at time t = 1
- value of cell (10 + (number of characters read at t)) at time t = 13
- cursor y at time t = 11
then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- value of cell 27 at time t = 1
- value of cell (10 + (number of characters read at t)) at time t = 13
- cursor y at time t = 11
then display text at x: x, y: y, and time: (t + 1) = display text at x: x, y: (y + 1), and time: t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- number of characters read at t < byte at ID: c, cell #26 at time t
then display text at x: (cursor x at time t), y: (cursor y at time t), and time: (t + 1) = byte at ID: c, cell #(10 + (number of characters read at t)) at time t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- number of characters read at t = byte at ID: c, cell #26 at time t
then cursor y at time (t + 1) = cursor y at time t
(link)if byte at ID: c, cell #27 at time t = 0, then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- cursor x at time t < 39
then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- cursor x at time t = 39
- cursor y at time t < 11
then cursor y at time (t + 1) = (cursor y at time t) + 1
(link)if cursor y at time t = 11, then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- cursor x at time t = 39
- cursor y at time t = 11
then display text at x: x, y: y, and time: (t + 1) = display text at x: x, y: (y + 1), and time: t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- byte at ID: c, cell #(10 + (number of characters read at t)) at time t = 13
- cursor y at time t < 11
then cursor y at time (t + 1) = (cursor y at time t) + 1
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- byte at ID: c, cell #(10 + (number of characters read at t)) at time t = 13
- cursor y at time t = 11
then cursor y at time (t + 1) = cursor y at time t
(link)if the following are true:
- byte at ID: c, cell #27 at time t = 1
- byte at ID: c, cell #(10 + (number of characters read at t)) at time t = 13
- cursor y at time t = 11
then display text at x: x, y: y, and time: (t + 1) = display text at x: x, y: (y + 1), and time: t
(link)
Comments
Please log in to add comments